2007
DOI: 10.1111/j.1365-2427.2007.01916.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the Redfield ratio infer nutrient limitation in the macroalga Spirogyra fluviatilis?

Abstract: 1. The cellular nutrient contents of microalgae, when growing at or approaching maximum rates, approximate the Redfield C : N : P (molar) ratio of 106 : 16 : 1. Deviations from this optimal ratio can be used to infer nutrient limitation of microalgal growth. However, this ratio may not be applicable to macroalgae, which are distinguished from microalgae by forming a thallus that is a discrete structure visible to the naked eye. The utility of the Redfield ratio to infer nutrient limitation of the growth of mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 33 publications
2
24
1
Order By: Relevance
“…Such low ratios were rarely measured for the streams in the present study, giving further credence to the conclusion that P was the limiting nutrient for littoral algal growth. In contrast to the Conesus Lake results, studies by Townsend et al (2008) on a tropical species of Spirogyra that inhabits streams and rivers of Australia indicated that both N and P could alternately limit growth. Optimal cellular N:P ratios for S. fluviatilis were 87:1, indicating a higher N requirement than predicted by the Redfield ratio of 16:1 that is typical of microalgae.…”
Section: Tributarycontrasting
confidence: 55%
See 2 more Smart Citations
“…Such low ratios were rarely measured for the streams in the present study, giving further credence to the conclusion that P was the limiting nutrient for littoral algal growth. In contrast to the Conesus Lake results, studies by Townsend et al (2008) on a tropical species of Spirogyra that inhabits streams and rivers of Australia indicated that both N and P could alternately limit growth. Optimal cellular N:P ratios for S. fluviatilis were 87:1, indicating a higher N requirement than predicted by the Redfield ratio of 16:1 that is typical of microalgae.…”
Section: Tributarycontrasting
confidence: 55%
“…The possibility that N limitation may be controlling filamentous algal cover in some sub-watersheds is interesting and plausible. In addition to the work of Townsend et al, (2008) showing variations in nutrient limitation on Spirogyra, mesocosm experiments with benthic algae, organisms that are often a few centimeters below surficial filamentous algae in the water column, have demonstrated that large amounts of N and P are removed from the water column and that both may be limiting for growth (Havens et al, 1999, McDougal et al, 1997. The design and consequently the results of the watershed manipulation experiments reported here do not allow or indicate whether N or P or both were limiting to littoral algal growth in Conesus Lake while correlation analyses have to be viewed as suggestive.…”
Section: Tributarymentioning
confidence: 97%
See 1 more Smart Citation
“…This has been found to be related to local-scale habitat factors such as canopy cover, river orientation and substrate, with higher photosynthetically active radiation (PAR) strongly correlated with higher GPP (Mulholland et al, 2001), and often greater productivity on cobble substrate compared with sand (Fellows et al, 2006). In Australia's wet-dry tropics during the dry season, most rivers are oligotrophic (Brodie & Mitchell, 2005) and PAR is often high and thus primary production has been shown to be nutrient-rather than light-or carbon-limited (Webster et al, 2005;Ganf & Rea, 2007;Townsend et al, 2008). Primary production and factors limiting production are generally measured in the dry season, and thus, knowledge of the dynamics in GPP and algal biomass over the annual cycle is limited.…”
Section: Introductionmentioning
confidence: 98%
“…Occasionally papers are published which include descriptions and bio-geographical information (Townsend et al 2008) but generally the baseline information is unavailable, being held in departmental records (Skinner 2008). It is rare to find published papers with detailed and floristic content (May andPowell 1986, Entwisle 1989a, b).…”
Section: Introductionmentioning
confidence: 99%